Long-Term Farming and Rural Demographic Trends - Anríquez, Gustavo (Washington, DC: World Bank, 2012)
Two general characteristics of rural populations are studied: farming operations at the global level and global rural demographic trends. Analysis of farming at the global level shows that agricultural land is expanding in Latin America and Africa, while expansion limits have been reached in South Asia. Roughly 90% of the worlds farms are small, defined as smaller than 2 hectares, especially in high density areas. While small farms tend to focus on staple crops, it is predicted that liberalization of agricultural markets resulting from future rounds of the WTO will not encourage these farms toward diversification. With respect to demographic trends, a superficial analysis of gender inequality shows that in rural Sub- Saharan Africa, inequality in terms of economic wellbeing and gender is more acute. AIDS is contributing to diminish femininity, not to intensify it and ageing is not really a concern for least developed countries. High dependency ratios brought about by larger population of children act to reduce rural wellbeing in the developing world. Therefore, the supply of labor is not at risk even in countries that are hard hit by AIDS. A cross-country migration analysis finds that only in Latin America is migration helping upward convergence of rural communities. Education is identified as the main asset that enables migration. Communities that are not endowed with sufficient levels of human capital are being left behind.